Transformative partnerships with university schools - Hatlevik, Ida Katrine Riksaasen; Eriksen, Tone Malmstedt; Hunskaar, Tove Seiness; Steele, Annfrid Rosøy; Unhjem, Astrid; Vedeler, Gørill Warvik (2024)
The establishment of transformative partnerships between a teacher education (TE) institution and a few selected “university schools” is widely recognized as a strategy to ensure the ongoing quality development of TE programs and to increase research-based development in schools. The University of Oslo and UiT The Arctic University of Norway were the first TE institutions in Norway to establish these kinds of close and committed partnerships with university schools, and they now have over 10 years of experience. In this chapter, we describe the institutions’ model for transformative partnerships with university schools and highlight important findings from research on various activities that have emerged from this collaboration. The findings indicate that in transformative partnerships where participants collaborate on the management, development, and implementation of TE and on research and development (R&D) in schools, university schools can influence the quality of TE programs. As such, university schools can make research in TE more relevant for themselves and can provide information about on-campus TE activities. Having close connections between schools and campuses also helps to ensure that student teachers will perceive the content of on-campus teaching as being relevant for their future professional practice as schoolteachers.